Novel Hemizygous Mutations of TEX11 Cause Meiotic Arrest and Non-obstructive Azoospermia in Chinese Han Population - Ji, Zhiyong; Yao, Chencheng; Yang, Chao; Huang, Chuan; Zhao, Liangyu; Han, Xia; Zhu, Zijue; Zhi, Erlei; Liu, Nachuan; Zhou, Zhi; Li, Zheng (Frontiers in Genetics, 2021)
Testis-expressed gene 11 (TEX11) mutation has been associated with non-obstructive azoospermia (NOA) and meiotic arrest. An analogous mutation of TEX11 in the mouse impairs meiosis and can be rescued by in vitro expansion of SSCs and gene therapy. However, a lack of genetic screening of a large cohort of Asian patients (including pedigree analysis) and proper functional evaluation limit the clinical application of TEX11 mutation screening. Thus, we performed whole-exome sequencing (WES) in 479 patients with NOA and identified three novel mutations (two splicing mutations and one missense mutation) in TEX11 in three pairs of siblings from three families and four novel pathogenic mutations (three frameshift mutations and a non-sense mutation) of TEX11 in four sporadic NOA-affected cases. Novel variants among family members were segregated by disease phenotype, and all the seven mutations were predicted to be pathogenic. Histological analysis showed that three patients with TEX11 mutations underwent meiotic arrest. The four mutations that resulted in protein truncations and defective meiosis-specific sporulation domain SPO22 were validated by Western blot. In total, we find seven of 479 patients of NOA (1.5%) carrying TEX11 mutations. Our study expands the knowledge of mutations of TEX11 gene in Asian patients with NOA. The high prevalence and X-linked inherited mode indicated that TEX11 might be included in genetic screening panels for the clinical evaluation of patients with NOA.